2007
DOI: 10.1038/sj.leu.2404643
|View full text |Cite
|
Sign up to set email alerts
|

The insulin-like growth factor-I receptor kinase inhibitor NVP-AEW541 induces apoptosis in acute myeloid leukemia cells exhibiting autocrine insulin-like growth factor-I secretion

Abstract: Insulin-like growth factor-I (IGF-I) and its receptor (IGF-IR) have been implicated in the pathophysiology of many human cancers, including those of hematopoietic lineage. We investigated the therapeutic potential of the novel IGF-IR tyrosine kinase activity inhibitor, NVP-AEW541, on human acute myeloid leukemia (AML) cells. NVP-AEW541 was tested on a HL60 cell subclone, which is dependent on autocrine secretion of IGF-I for survival and drug resistance, as well as primary drug resistant leukemia cells. NVP-AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 47 publications
4
68
0
Order By: Relevance
“…Thus, IGF-1 signaling may be responsible for b-catenin stability or it may cooperate with Bcr-Abl to further enhance b-catenin stability. Additional support for the role of IGF-1 signaling in self-renewal comes from the ability of exogenous IGF-1 to increase the clonogenic capacity in AML CD34 þ cells expressing IGF-1R (Tazzari et al, 2007). Our study reveals Bcr-Abl/Hck/Stat5b as a key pathway for regulating IGF-1 expression in CML BC cell lines.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Thus, IGF-1 signaling may be responsible for b-catenin stability or it may cooperate with Bcr-Abl to further enhance b-catenin stability. Additional support for the role of IGF-1 signaling in self-renewal comes from the ability of exogenous IGF-1 to increase the clonogenic capacity in AML CD34 þ cells expressing IGF-1R (Tazzari et al, 2007). Our study reveals Bcr-Abl/Hck/Stat5b as a key pathway for regulating IGF-1 expression in CML BC cell lines.…”
Section: Discussionsupporting
confidence: 52%
“…As described above, IGF-1 is required in many stages of hematopoiesis and deregulation of IGF-1R activation may be a driving event for the CP to BC transition. Recently it has been shown that IGF-1R inhibitors AG1024 (Deutsch et al, 2004) and NVP-AEW541 (Doepfner et al, 2007;Tazzari et al, 2007) have strong activity against CML and AML cells with autocrine IGF-1 secretion, respectively. We also observed that AG1024 inhibited viability, proliferation and enhanced apoptosis in CML BC cell lines with high IGF-1 expression (K562 and KU812) and showed weaker activity against our low IGF-1-expressing CML BC cell line (JURL-MK1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] In addition, upregulation can occur through abnormal autocrine/paracrine secretion of IGF-1 or vascular endothelial growth factor (VEGF), overexpression of PBKp100β, PI3Kp100δ or PDK1, or underexpression of protein phosphatase 2 (PP2A). [161][162][163][164][165][166][167][168] Unlike T-ALL, PTEN inactivation in AML is a very rare mechanism of AKT activation. [159,160] As with ALL, rapalogs were the first agents to be studied in AML.…”
Section: Acute and Chronic Myelogenous Leukemiamentioning
confidence: 99%
“…7 Activation of the phosphatidylinositol 3-kinase (PI3K)/Aktsignaling pathway is another key factor, which plays a central role in cancer biology, conferring resistance both in vivo and in vitro to therapeutic treatments of various types of malignancies. [8][9][10] Upon activation by different stimuli, membrane localization of PI3K generates phosphatidylinositol-3,4,5-trisphosphate, which then activates a number of downstream substrates. 11 The serine/ threonine kinase Akt is a well-characterized PI3K target, and binding of phosphatidylinositol-3,4,5-trisphosphate to the pleckstrin homology domain of Akt results in its translocation to the plasma membrane, where it undergoes phosphorylation at both Thr308 and Ser473.…”
Section: Introductionmentioning
confidence: 99%